Modeling ionic transport through ion-exchange membranes - Cerrillo-González, María del Mar; Villén-Guzmán, María Dolores; Paz-García, Juan Manuel (My University, 2022)
Electrodialysis (ED) is a membrane separation process in which ions are transferred through selective ion-exchange membranes (IEMs) from one solution to another using an electric field as the driving force. ED is a mature technology in the field of brackish water desalination, but in the last decades, the development of new membranes has allowed to extend its application in the food, drug, and chemical process industry, as well as in the environmental engineering field. The effectiveness of ED separation depends on numerous variables, including cell properties membranes properties and operational parameters (electric current; electrical resistance of IEMs and electrolyte; pH and concentration). All these parameters are interrelated between them, and the study of their effect is important to design and optimize the process. A key factor to understand the process is the ions transport through the IEMs, together with the concentration and potential profile create in the boundary layer between the electrolyte and the membrane charged surface.
Keywords: Membranas intercambiadoras de iones; COMSOL Multiphysics (Software); Modelado multifísico; Ion exchange membrane; COMSOL Multiphysics; Modeling